ANALISA SEBARAN DAN KEBUTUHAN PASAR BERDASARKAN STANDAR LINGKUNGAN DI KOTA SURABAYA - Aristyanto, Erwan (Jurnal Riset Inossa : Media Hasil Riset Pemerintahan, Ekonomi dan Sumber Daya Alam, 2024)
The aim of this research is to analyze the conditions, needs and availability of traditional markets in the city of Surabaya, so that we can find out how many neighborhood-scale community markets are needed by the people of Surabaya, what is the current availability of the number of people's markets in the city of Surabaya and what the current condition is related to. with SNI 8152:2015 concerning People's Markets. The research method used is descriptive research using a survey. Descriptive research can be interpreted as a problem-solving process that is investigated by describing the current state of the subject and object of research based on visible facts or how they are. The implementation of descriptive research methods is not limited to collecting and compiling data, but includes analysis and interpretation of the data, apart from that everything collected can be the key to what is being studied. The population in this research is all traditional markets built by the private sector and the Surabaya City Government. where its existence is one of the most obvious indicators of community economic activity in a region. The samples taken were 15 markets consisting of 7 markets under the auspices of PD Pasar, 4 markets under the auspices of the Cooperative Department and 5 private markets by dividing 2 questionnaires, namely for manager respondents and market trader respondents, where 1 respondent was taken for the manager and 8 traders were taken as representatives of groups of traders based on the group of goods being sold. (sellers of vegetables, fruit, meat, fish, oil & spices, rice & tubers, food and drink and various other goods). Results: The distribution of the number of traditional markets throughout the Surabaya region has a total excess of 90 traditional markets for comparison with environmental market standards that have been met (30,000 people/market). And based on a map of traditional market location points based on coordinate points / Global Positioning System (GPS), it shows that the distribution of traditional markets is not evenly distributed, especially in the South Surabaya and West Surabaya areas.